EFFECT OF POSTOPERATIVE EPIDURAL ANALGESIA AFTER MAJOR ORTHOPEDIC SURGERIES, A RETROSPECTIVE STUDY - Pathak, Laxmi (Journal of Universal College of Medical Sciences, 2016)
INTRODUCTION: Epidural analgesia has been used in many major surgeries like upper abdominal surgery, cardio-thoracic surgery, orthopedic surgery etc. Epidural analgesia is one of the commonly used methods of postoperative pain control despite its associated complications. So, this study was conducted to find out its effectiveness in major orthopedic surgeries done in Universal College of Medical Sciences. MATERIAL AND METHODS: A retrospective study was done at Universal College of Medical Sciences & Teaching Hospital, Bhairahawa, Nepal from July 2012 to June 2014. Data of 57 patients, aged between 17 to 91 years having American Society of Anesthesiologists (ASA) physical status 1 and 2 who had undergone major orthopedic surgeries under spinal anesthesia and lumber epidural catheterization were collected and important information regarding anesthesia and surgery, epidural catheter and postoperative epidural analgesia, any complications if occurred throughout the study period were recorded. Departmental Protocol for epidural analgesia was followed in these patients. Patients who received intraoperative epidural anesthesia or analgesia and any other anesthetic or analgesic agents were excluded in this study. RESULTS: This study found epidural analgesia, a very effective way to relieve pain in patients undergoing major orthopedic surgeries, when given according to the Departmental Protocol. There were no any complications related to epidural analgesia till 4th postoperative day. Out of 57, only 2 patients received injection Ketorolac intravenously as a rescue analgesic at the same day of operation before epidural top up. Average time to demand for analgesic after the last dose of epidural top up was 21.933 hours. All patients were mobilized around their beds on 2nd postoperative day. The average postoperative days of hospital stay was only 6.5 days. CONCLUSION: Epidural mixture of Bupivacaine-morphine in lower dose and concentration given as an intermittent bolus dosing via lumber epidural catheter is safe and very effective in relieving postoperative pain after major orthopedic surgeries without any significant complications. Journal of Universal College of Medical Sciences (2015) Vol.03 No.02 Issue 10